Tetap Nyaman di Tengah Ketidakadilan: Pembinaan Iman Berdasarkan Mazmur 7:1-18 di GKB Bahtera Hayat Semarang - Ragil Kristiawan (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2024)
Several members of the GKB Bahtera Hayat Semarang congregation felt injustice both in their families and at work because of their faith in the Lord Jesus Christ. It is against this background that the Pastor initiated faith training activities for the local congregation. This faith training activity is entitled: remaining comfortable in the midst of injustice based on Psalm 7 which will be held on Sunday, 14 July 2024 at GKB Bahtera Hayat, Jl. Ketileng Asri VII/E.106 Semarang. In preparing this faith training, the service uses a literature study method to carry out an exposition of Psalm 7. Meanwhile, in carrying out the service, the service uses an interactive lecture method. The results of the exposition of psalm chapter 7 show three things about how God's people remain comfortable in injustice. First, continue to take refuge in the just God (vv. 2-11). Second, continue to hope in God's justice alone (vv. 12-17). And third, remain grateful for God's justice because His justice will definitely be revealed (v. 18). The results of this PkM evaluation show that the congregation is satisfied and very satisfied with the faith training material, presentation, and exposition results of Psalm 7.